The Potential of Dryland as An Area of Agro-Tourism and Kalimantan’s Local Fruit Producing for Buffer New National Capital Region - I Gede Kariasa; Zein Andri Faisal Akmal; Andini Putri Syawalluna; Riza Adrianoor Saputra; Noor Laili Aziza; Muhammad Noor (Gontor Agrotech Science Journal, 2023)
Dry land in Kalimantan has a potential area of 41.61 million ha or 29% of the area in Indonesia of around 144.47 million ha which can be developed for agriculture, plantations, and forestry. Dry land has the potential to be developed for annual crops such as fruit forest plants. Welcoming Kalimantan as the National Capital City (IKN), the development of agro-tourism and local fruit production in Kalimantan as a buffer zone for food security has national and international strategic and political values. Agro-tourism is prepared based on conservation and environmental preservation, especially local Kalimantan fruit. The steps needed to develop local Kalimantan fruit agro-tourism are determining land, making ponds, determining types of local fruit commodities, land and landscape arrangement, land preparation, selecting superior seeds, plant care, empowering local human resources, building facilities and infrastructure, promotion and partnerships, as well as the grand opening. There are several divisions of land in the Kalimantan local fruit agro-tourism area, on the mainland, namely local fruit preservation land, forest areas located on the outermost part of agro-tourism, determining the location of ponds as water sources, camping areas for visitors who want to stay overnight, as well as culinary areas. The dry land used will be planted with horticultural commodities for the first five years to fill the land until the local fruit produces fruit. Furthermore, local fruit preservation will be determined to realize Kalimantan local fruit agro-tourism. The existence of local fruit agro-tourism in Kalimantan will become a new icon for national agro-tourism, education, and environmental preservation for the archipelago. Government and community support regarding the development of local Kalimantan fruit agro-tourism is urgently needed.